Precise detection of tiny birefringence with accuracy reaching 10−11 level - Xiliang Zhang; Yanwen Hu; Shiwen Zhou; Zepei Zeng; Guohua Liu; Haolin Lin; Zhen Li; Zhenqiang Chen; Shenhe Fu (Nature Communications)
Abstract High-precision birefringence detection is crucial in many fundamental and applied research fields such as chirality detection, optical clocks and quantum information. Although numerous techniques have been demonstrated to detect birefringence in optical materials, the current detection precision typically remains at 10−8. Here we introduce a different physical mechanism for birefringence detection in the classical regime, achieving an accuracy at the 10−11 level. Our technique uses an effective photonic two-level system, dynamically driven by a birefringence-sensitive synthetic magnetic field created by propagation-invariant spin-orbit-coupled structured light in the subwavelength regime. The magnetic field equivalent induces the Rabi oscillation of photonic state, manifested as a nontrivial periodic spin-orbital angular momentum conversion. The ultrahigh detection precision arises from high-birefringence-sensitive topological transition between different oscillatory modes with high Rabi frequencies. The detection precision is tunable by controlling envelope size of structured light at the subwavelength scale. Our technique benefits a broad range of applications involving optical birefringence.